LONG-TERM ENSURE RELIABLE, QUALITY AND AFFORDABLE ELECTRICITY FOR THE CONSUMERS - N. Lyubimova (Вестник университета)
The article deals with current issues of reliability, quality and availability of power. Introduction assessment grid companies in terms of frequency and duration of outages for stimulating increasing the reliability of electricity supply. Using the integral index of the quality of energy service the final consumers. Accounting for tariff regulation of electricity networks the service reliability and quality indicators of consumers. Significant reduction of time, cost and approval procedures for grid connection to the electrical network, especially for the small and medium-sized businesses. To work on the entry in the top-20 on the grid connection.